2021
DOI: 10.1111/ajad.13243
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use at the intersection of sexual orientation and gender identity in a representative sample of youth in Colorado

Abstract: Background and Objectives Lesbian, gay, bisexual, and questioning (LGBQ) youth are at greater risk of problematic alcohol use than their heterosexual peers, yet there is a dearth of research examining variability in alcohol use among youth that simultaneously accounts for sexual orientation and gender identity. This paper examines the relationship between alcohol use and intersecting identities of sexual orientation and gender while accounting for this population's disproportionate experiences of depression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The current lack of measurement and reporting of sample gender information [85] makes it difficult to know for example whether trans and/or nonbinary individuals were included and whether the authors assessed sex assigned at birth (suggested by the use of "male"/ "female" terminology) or gender identity ("men"/ "women" terminology). More transparent and rigorous reporting of gender and inclusion of more than one gender and sexual orientation group in studies on PPU is especially important when we consider that these person characteristics have been shown to interact with other behavioral addictions as well as substance abuse [86][87][88]. An issue complicating the integration of findings across experiments is the diversity of stimuli.…”
Section: Limitationsmentioning
confidence: 99%
“…The current lack of measurement and reporting of sample gender information [85] makes it difficult to know for example whether trans and/or nonbinary individuals were included and whether the authors assessed sex assigned at birth (suggested by the use of "male"/ "female" terminology) or gender identity ("men"/ "women" terminology). More transparent and rigorous reporting of gender and inclusion of more than one gender and sexual orientation group in studies on PPU is especially important when we consider that these person characteristics have been shown to interact with other behavioral addictions as well as substance abuse [86][87][88]. An issue complicating the integration of findings across experiments is the diversity of stimuli.…”
Section: Limitationsmentioning
confidence: 99%